Quail Eggs (Coturnic coturnic japonica)'s Fertility, Hatching Power, Hatching Weight, and Saleable DOQ at Quail Farm - Nova, Tertia Delia; Azhar; Misbah (Andalasian Livestock, 2025)
This study aims to determine the level of fertility, hatchability, hatching weight, and saleable DOQ of quail eggs (Coturnix coturnix japonica) at puyuh Farm. This study used 16-week-old quails kept in 5 battery cages, in one cage there are 5 levels with a sex ratio of 1:4. Village, Payakumbuh Timur District, Payakumbuh City, West Sumatra. This study used 450 quail eggs which were collected randomly from 5 battery cages, each cage was taken 3 levels for 4 days of collection. This study used a survey method by means of observation and descriptive data analysis. The parameters observed were egg weight, fertility, hatchability, hatching weight and saleable DOQ. The results of this study obtained an average egg weight of 11.25 ± 0.80 g, an average fertility of 85.56 ± 10.13%, an average hatching power of 77.77 ± 12.00%, an average hatching weight of 7.53 ± 0.94 g, and a saleable DOQ of 87.58 ± 9.11%, because there were DOQs with physical defects in the form of deformed and weak legs. The conclusion of this study was that quail eggs at Farm produced standard egg weights, high fertility, high hatching power, standard hatching weights, and high saleable DOQ. However, in the maintenance of seeds at this farm, only female seeds are sold.